2009
DOI: 10.1016/j.crci.2009.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activity of methanolic extracts and some bioactive compounds of Atriplex halimus

Abstract: For the first time, we have evaluated the antioxidant properties of principal secondary metabolites of leaves and stems from Atriplex halimus. The leaves methanolic extract contained higher levels of total phenolic (10.12 AE 0.56 mg GAE/g DW) than stems methanolic extract (3.77 AE 0.19 mg GAE/g DW). The leaves flavonoids represented by ethyl acetate and butanolic fractions have more hydrogen donating ability to reducing iron and the higher DPPH radical scavenging activity. To cite this article: N.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
4
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(72 citation statements)
references
References 30 publications
2
56
4
1
Order By: Relevance
“…The cell viability remained above 85% at relatively high concentrations, indicating that LAECs and Cs1 were non-toxic to human leukocytes. Antioxidant tests were performed using a DPPH assay; this is a widely accepted method for evaluation of in vitro antioxidant activity of extracts and is based on the capacity of antioxidant compounds present in the sample to capture DPPH radicals (Benhammou, Bekkara, Panovska, 2009;Ayala-Zavala et al, 2012;Mohsin, Mahadevan, Kurup, 2014;Wan-Ibrahim, Sidik, Kuppusamya, 2010). The results showed that LAECs and Cs1 inhibited ≥ 50% of radicals at concentrations of 10 µg/mL and 50 µg/ mL, showing that both samples appear to protect the studied biological matrix, since the concentrations tested were able to neutralize the radical DPPH.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The cell viability remained above 85% at relatively high concentrations, indicating that LAECs and Cs1 were non-toxic to human leukocytes. Antioxidant tests were performed using a DPPH assay; this is a widely accepted method for evaluation of in vitro antioxidant activity of extracts and is based on the capacity of antioxidant compounds present in the sample to capture DPPH radicals (Benhammou, Bekkara, Panovska, 2009;Ayala-Zavala et al, 2012;Mohsin, Mahadevan, Kurup, 2014;Wan-Ibrahim, Sidik, Kuppusamya, 2010). The results showed that LAECs and Cs1 inhibited ≥ 50% of radicals at concentrations of 10 µg/mL and 50 µg/ mL, showing that both samples appear to protect the studied biological matrix, since the concentrations tested were able to neutralize the radical DPPH.…”
Section: Discussionmentioning
confidence: 99%
“…Under normal conditions, reactive oxygen species (ROS) are an essential part of such processes, and the most common ROS include the superoxide anion (O 2 −• ), hydrogen peroxide (H 2 O 2 ), peroxyl radicals (ROO • ), and reactive hydroxyl radical (HO • ) (Benhammou, Bekkara, Panovska, 2009;Gaur et al, 2009). The imbalance between free radical production and endogenous detoxification systems (predominantly non-enzymatic and enzymatic antioxidants) can lead to oxidative stress.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For flavonoids extraction, the method of Benhammou et al (2009) was applied; thus, 20 g of the dry powder of L. halimifolium Mill leaves was extracted in 200 mL of methanol for 24h at room temperature. The extracts were concentrated in a rotary evaporator at 60°C under a reduced pressure.…”
Section: Extraction Proceduresmentioning
confidence: 99%
“…After filtration through filter paper, the resulting solution was evaporated under vacuum at 60°CbyBuchi RotavaporR-200dry. The residue was then dissolved in 3mL of methanol 13 .…”
Section: Preparation Of Methanolic Extractsmentioning
confidence: 99%